A possible role of dystrophin in neuronal excitability: A review of the current literature. (April 2015) - Hendriksen, Ruben G.F.; Hoogland, Govert; Schipper, Sandra; Hendriksen, Jos G.M.; Vles, Johan S.H.; Aalbers, Marlien W.
Highlights: Epilepsy is more frequently observed in muscular dystrophy (MD) populations. Initial experimental research confirms altered levels of dystrophin in epilepsy. Seizure generation thresholds seem to be different in animal models of MD. A lack of dystrophin in the CNS might contribute to hyperexcitation. Abstract: Duchenne muscular dystrophy (DMD) is a recessive hereditary form of muscular dystrophy caused by a mutation in the dystrophin gene on the X chromosome. Clinical observations show that in addition to progressive muscular degeneration, DMD is more often accompanied by neurocognitive symptoms and learning disabilities, especially in automatisation of reading, attention processes, and expressive language skills. Additionally, three studies reported a higher prevalence of epilepsy in DMD, suggesting that the absence of dystrophin might be related to increased CNS excitability. In this article, we aim to review current clinical and experimental evidence for a potential role of brain dystrophin in seizure generation.